Fetal Growth Restriction - Castillo-Urquiaga, Walter (2019)
Fetal Growth Restriction (FGR) is an abnormal growth associated with adverse prognosis in the short, medium and long term. Etiological factors may be acting synergistically and therefore the use of multiple parameters is useful in diagnosis. The detection, monitoring and management depend on knowledge of the new terminology and parameters for identification that is related to clinical presentation and progression in relation to gestational age and from its etiology. We describe the typical presentations of early and late FGR and the need to differentiate the normal constitutionally small (NCS).